1989
DOI: 10.1136/bmj.299.6691.91
|View full text |Cite
|
Sign up to set email alerts
|

Is excessive running predictive of degenerative hip disease? Controlled study of former elite athletes.

Abstract: Press, 1984:211-24

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
92
0
4

Year Published

1991
1991
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(101 citation statements)
references
References 15 publications
3
92
0
4
Order By: Relevance
“…Recent studies of runners (25)(26)(27)(28) reported that those who were highly physically active may face an increased risk of radiographic OA. Several small longitudinal studies (29,30) have shown no increased OA risk in runners.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of runners (25)(26)(27)(28) reported that those who were highly physically active may face an increased risk of radiographic OA. Several small longitudinal studies (29,30) have shown no increased OA risk in runners.…”
Section: Discussionmentioning
confidence: 99%
“…In a study from Switzerland, the entire national team in long-distance running (27 men) and bobsleigh (9 men) and a control group of 23 men were examined in 1973 and re-examined in 1988 (Marti et al 1989). All were free from arthrosis in 1973 but, 15 years later, 5 of the runners and none of the controls showed radiographic signs of hip arthrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies that have examined former recreational and professional athletes have shown a positive correlation between various sports participation and an increased prevalence of hip OA (33)(34)(35)(36)(37)(38)(39)(40)(41). A retrospective case-control study of regular high-mileage, long-distance male runners who were longitudinally followed for 15 years found radiologic evidence of OA consisting of subchondral sclerosis (59%) and osteophyte formation (29%) in their cohort (39). Additionally, 30% of these runners at age 42 years had symptomatic hip pain, and their long-term, high-intensity, high-mileage running was found to be statistically equivalent to age as a risk factor for the development of radiographic hip OA and symptomatic hip pain.…”
mentioning
confidence: 99%